Pemikiran Tasawuf Hamzah Fansuri - Mirza Fauziah (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
This article examines about the personal of Hamzah Fansuri as a tasauf  scholars. His thinking is very significant in this field and can be part is very  strategic. He lived in the middle of seventeenth century (XVI-XVII) is seen by  some scientists as a reformer. He contributed significantly to the development of  islamic culture, particularly in the fields of spirituality, philosophy of science,  literature and languages at once. Sharp criticism of the political and moral conduct  of the kings, Nobles and rich people put him as a courageous intellectual of his  time to the palace of Aceh is not so fond of his activities and his followers.  Hamzah Fansuri leaving many good works of prose and poetry of sufi. Therefore,  his tasauf thinking can be many scientists study.